(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
The state of knowledge research carried out in this study aimed to investigate the national productions available in the Theses and Dissertations Database related to gamification in education and, more specifically, in Biology teaching. Using a bibliographic research approach, academic papers were identified and analyzed that address the application of gamification in the Brazilian educational context in this school subject. In this way, it was possible to identify trends, gaps, and predominant areas of focus in national productions on gamification methodology, contributing to a more comprehensive understanding of the practices and perspectives of Brazilian researchers in this field. In addition, the analysis of the bibliographical references made it possible to establish connections between the different studies and theories that underpin the use of gamification as a teaching methodology. As a result, this study offers a synthesis of the main research findings in the area, providing a solid basis for the development of future research and educational practices related to gamification in Biology teaching in a Brazilian context.